A proof of completeness of the Green-Lamé type solution in thermoelasticity - D. S. Chandrasekharaiah (International Journal of Mathematics and Mathematical Sciences)
A proof of completeness of the Green-Lamé type solution for the unified governing field equations of conventional and generalized thermoelasticity theories is given.